Effects of switching weekly alendronate or risedronate to monthly minodronate in patients with rheumatoid arthritis: a 12-month prospective study - Ebina, K.; Noguchi, T.; Hirao, M.; Hashimoto, J.; Kaneshiro, S.; Yukioka, M.; Yoshikawa, H. (Osteoporosis international, 2016)
Summary Switching weekly ALN or RIS to monthly MIN in patients with RA, of whom two-thirds were treated with low-dose PSL, significantly decreased bone turnover markers and increased BMD at 12 months, suggesting that monthly MIN may be an effective alternative treatment option of oral bisphosphonate treatment. Introduction The aim of this prospective, observational study was to evaluate the effects of switching weekly alendronate (ALN 35 mg) or risedronate (RIS 17.5 mg) to monthly minodronate (MIN 50 mg) in patients with rheumatoid arthritis (RA). Methods Patient characteristics were as follows: n = 172; 155 postmenopausal women, age 65.5 (44–87) years; T-score of lumbar spine (LS), −1.4; total hip (TH), −1.8; femoral neck (FN), −2.1; dose and rate of oral prednisolone (2.3 mg/day), 69.1 %; prior duration of ALN or RIS, 46.6 months; were allocated, based on their preference, to either the (1) continue group ( n = 88), (2) switch-from-ALN group ( n = 44), or (3) switch-from-RIS group ( n = 40). Results After 12 months, increase in BMD was significantly greater in group 3 compared to group 1: LS (4.1 vs 1.2 %; P < 0.001), TH (1.9 vs −0.7 %; P < 0.01), and FN (2.7 vs −0.5 %; P < 0.05); and in group 2 compared to group 1: LS (3.2 vs 1.2 %; P < 0.05) and TH (1.5 vs −0.7 %; P < 0.01). The decrease in bone turnover markers was significantly greater in group 3 compared to group 1: TRACP-5b (−37.3 vs 2.5 %; P < 0.001), PINP (−24.7 vs −6.2 %; P < 0.05), and ucOC (−39.2 vs 13.0 %; P < 0.05); and in group 2 compared to group 1: TRACP-5b (−12.5 vs 2.5 %; P < 0.05) at 12 months. Conclusions Switching weekly ALN or RIS to monthly MIN in patients with RA may be an effective alternative treatment option of oral bisphosphonate treatment.